Analyze The Effect of Current Ratio, Leverage Ratio and Profitability Ratio to Stock Price in Indonesıa Stock Exchange - Angelin Angelin; Haposan Banjarnahor (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
This study raises a topic that aims to analyze the effect of current ratios, debt ratios and profitability ratios on stock prices in the consumer goods sector. The sample data used is panel data with a time series time scale at the 2017-2021 financial statement interval. Sample data was collected from secondary data sources by accessing the Indonesia Stock Exchange (IDX) page. The purpose of this research to figure out is there any effect of independent variable to dependent variable. If there’s any significant effect found out in this research, it might help investors to predict the stock prices of listed company. However, The results found in this study include the current ratio, debt to asset ratio (DAR), and ROA do not have a significant effect on stock prices. This is because there are many other factors that significantly influence the rise and fall of stock prices. In addition, this insignificant effect can be caused by the condition of the company's profit which is not in optimal condition considering the data that taken as sample include a period when the COVID-19 pandemic is rife in Indonesia.